Pediatric Phalanx Fractures. Issue 11 (November 2016) - Abzug, Joshua M.; Dua, Karan; Bauer, Andrea Sesko; Cornwall, Roger; Wyrick, Theresa O.
Abstract : Phalangeal fractures are the most common type of hand fracture that occurs in the pediatric population and account for the second highest number of emergency department visits for fractures in the United States. The incidence of phalangeal fractures is the highest in children aged 10 to 14 years, which coincides with the time that most children begin playing contact sports. Younger children are more likely to sustain a phalangeal fracture in the home setting as a result of crush and laceration injuries. Salter-Harris type II fractures of the proximal phalanx are the most common type of finger fracture. An unmineralized physis is biomechanically weaker compared with the surrounding ligamentous structures and mature bone, which makes fractures about the physis likely. A thorough physical examination is necessary to assess the digital cascade for signs of rotational deformity and/or coronal malalignment. Plain radiographs of the hand and digits are sufficient to confirm a diagnosis of a phalangeal fracture. The management of phalangeal fractures is based on the initial severity of the injury and depends on the success of closed reduction techniques. Nondisplaced phalanx fractures are managed with splint immobilization. Stable, reduced phalanx fractures are immobilized but require close monitoring to ensure maintenance of fracture reduction. Unstable, displaced phalanx fractures require surgical management, preferably via closed reduction and percutaneous pinning.